Introducing Crossover in SLIM-GSGP - Pietropolli, Gloria (2025)
Pietropolli, G., Farinati, D., Manzoni, L., Castelli, M., Silva, S., & Vanneschi, L. (2025). Introducing Crossover in SLIM-GSGP. In B. Xue, L. Manzoni, & I. Bakurov (Eds.), Genetic Programming: 28th European Conference, EuroGP 2025, Held as Part of EvoStar 2025, Trieste, Italy, April 23–25, 2025, Proceedings (pp. 103-119). (Lecture Notes in Computer Science; Vol. 15609). Springer Nature Switzerland AG. https://doi.org/10.1007/978-3-031-89991-1_7 --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 (DOI: 10.54499/UIDB/04152/2020) - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS),(https://doi.org/10.54499/UIDB/04152/2020) the project 2024.07277. IACDC, and the LASIGE Research Unit, ref. UID/000408/2025.